Gambogic amide inhibits angiogenesis by suppressing VEGF/VEGFR2 in endothelial cells in a TrkA-independent manner - Tongtong Sui (Taylor & Francis Group, 2021)
Context Gambogic amide (GA-amide) is a non-peptide molecule that has high affinity for tropomyosin receptor kinase A (TrkA) and possesses robust neurotrophic activity, but its effect on angiogenesis is unclear. Objective The study investigates the antiangiogenic effect of GA-amide on endothelial cells (ECs). Materials and methods The viability of endothelial cells (ECs) treated with 0.1, 0.15, 0.2, 0.3, 0.4, and 0.5 μM GA-amide for 48 h was detected by MTS assay. Wound healing and angiogenesis assays were performed on cells treated with 0.2 μM GA-amide. Chicken eggs at day 7 post-fertilization were divided into the dimethyl sulfoxide (DMSO), bevacizumab (40 μg), and GA-amide (18.8 and 62.8 ng) groups to assess the antiangiogenic effect for 3 days. mRNA and protein expression in cells treated with 0.1, 0.2, 0.4, 0.8, and 1.2 μM GA-amide for 6 h was detected by qRT-PCR and Western blots, respectively. Results GA-amide inhibited HUVEC (IC50 = 0.1269 μM) and NhEC (IC50 = 0.1740 μM) proliferation, induced cell apoptosis, and inhibited the migration and angiogenesis at a relatively safe dose (0.2 μM) in vitro. GA-amide reduced the number of capillaries from 56 ± 14.67 (DMSO) to 20.3 ± 5.12 (62.8 ng) in chick chorioallantoic membrane (CAM) assay. However, inactivation of TrkA couldn’t reverse the antiangiogenic effect of GA-amide. Moreover, GA-amide suppressed the expression of VEGF and VEGFR2, and decreased activation of the AKT/mTOR and PLCγ/Erk1/2 pathways. Conclusions Considering the antiangiogenic effect of GA-amide, it might be developed as a useful agent for use in clinical combination therapies.